Bacterial Artificial Chromosomes Volume 2: Functional Studies - Zhao, Shaying.; Zhao, Shaying.; Stodolsky, Marvin.; Stodolsky, Marvin. (Methods in Molecular Biology, 2004)
The ability to transfer and maintain DNA both within and between species is an essential skill in biotechnology and medicine. In Bacterial Artificial Chromosomes, expert investigators describe not only the classic methods, but also the many novel techniques they have perfected for the transfer of large DNAs into the cells of both microbes and animals via large-insert recombinant DNAs. Volume 2: Functional Studies provides a wide variety of methods and applications for functional analysis of the DNA-transformed organisms. The laboratory protocols follow the successful Methods in Molecular Biology™ series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Besides protocols, each chapter includes scientific reviews, software tools, database resources, genome sequencing strategies, and illustrative case studies. An accompanying volume, Volume 1: Library Construction, Physical Mapping, and Sequencing, presents readily reproducible techniques for library construction, physical mapping, and sequencing. Comprehensive and cutting-edge, the two volumes of Bacterial Artificial Chromosomes provide a superlative collection of highly productive protocols that will prove useful to many bioscientists, including genome sequencers, geneticists, molecular biologists, and biochemists studying the structure and function of specific genomes.